Tricuspid regurgitation, right ventricular function, and renal congestion: a cardiorenal triangle - Forado-Benatar, Ilana; Caravaca-Pérez, Pedro; Rodriguez-Espinosa, Diana; Guzman-Bofarull, Joan; Cuadrado-Payán, Elena; Moayedi, Yasbanoo; Broseta, José Jesús; Farrero, Marta (Frontiers in Cardiovascular Medicine, 2023)
There is a growing interest in the evaluation of tricuspid regurgitation due to its increasing prevalence and detrimental impact on clinical outcomes. Historically, it has been coined the “forgotten” defect in the field of valvular heart disease due to the lack of effective treatments to improve prognosis. However, the development of percutaneous treatment techniques has led to a new era in its management, with promising results and diminished complication risk. In spite of these advances, a comprehensive exploration of the pathophysiological mechanisms is essential to establish clear indications and optimal timing for medical and percutaneous intervention. This review will address the most important aspects related to the diagnosis, pathophysiology and treatment of tricuspid regurgitation from a cardiorenal perspective, with a special emphasis on the interaction between right ventricular dysfunction and the development of hepatorenal congestion.